Aerobic power of wheelchair handball players in a court test - Flores, Lucinar J. Forner (2011)
This study aimed to evaluate the aerobic power of Wheelchair Handball players through a method of field test (12 minutes). The sample of this study was of nine persons (n=9), affected by several physical disabilities, such as the sequel of poliomyelitis (n=4), spinal cord injury (n=3), lower limb amputation (n=1) and syndrome Charcot-Marie Tooth disease (n=1). The test consisted to go through a 12 minutes route of 25 x 15 meters, using the specific wheelchair for doing sports, and each athlete used his own chair. By distance, we calculated the estimated value of VO2max, according to the protocol of Franklin et al. (1990). The statistical analysis was made using SPSS 9.0 with value of p<0.05. The medium value of VO2max found was 22.79 (± 5.12) ml.kg.min-1, with minimum value of 12.2 and maximum of 29.47 ml.kg.min-1. In relation to heart rate, were found significant differences between the moments of rest, final and recovery of the test. These results, according to the classification of Franklin et al. (1990), show an average level of conditioning for this group studied.